2021
DOI: 10.21873/anticanres.14968
|View full text |Cite
|
Sign up to set email alerts
|

Direct-acting Antiviral Therapy Improves the Outcome of Chronic Hepatitis C/intermediate-stage B Hepatocellular Carcinoma Patients

Abstract: Background/Aim: The benefit of direct-acting antiviral therapy (DAA) in chronic hepatitis C (CHC) infected patients who received curative treatment for early-stage hepatocellular carcinoma (HCC) is well known, but is unclear for intermediate stage HCC. Patients and Methods: CHC patients with Barcelona Clinic Liver Cancer (BCLC) stage B HCC receiving chemoembolization were identified. Univariate, multivariate analyses, and Kaplan-Meier curve were used to identify factors associated with survival outcomes. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Although the current evidence strongly supports that HCV eradication therapy can be helpful toward reducing the risk of tumor recurrence and improving the rate of patient survival amongst patients with HCCs in BCLC stage 0/A [3, 4, 24, 25], some studies have also suggested that HCV antiviral therapy may be beneficial to patients with unresectable HCCs. In a retrospective cohort study for HCC patients in BCLC stage B, the median patient survival time was significantly longer in DAA-treated patients, when compared to that in DAA-untreated patients (40.1 vs. 22.9 months) [26]. Moreover, in a retrospective cohort study for HCC patients in BCLC stage C, whose HCCs were treated with sorafenib, HCV eradication through DAA therapy also confirmed patient survival benefits [27].…”
Section: Discussionmentioning
confidence: 95%
“…Although the current evidence strongly supports that HCV eradication therapy can be helpful toward reducing the risk of tumor recurrence and improving the rate of patient survival amongst patients with HCCs in BCLC stage 0/A [3, 4, 24, 25], some studies have also suggested that HCV antiviral therapy may be beneficial to patients with unresectable HCCs. In a retrospective cohort study for HCC patients in BCLC stage B, the median patient survival time was significantly longer in DAA-treated patients, when compared to that in DAA-untreated patients (40.1 vs. 22.9 months) [26]. Moreover, in a retrospective cohort study for HCC patients in BCLC stage C, whose HCCs were treated with sorafenib, HCV eradication through DAA therapy also confirmed patient survival benefits [27].…”
Section: Discussionmentioning
confidence: 95%
“…[1] Direct-acting antivirals (DAA) revolutionised HCV clinical management since their introduction. [2,3] Tuberculosis is responsible of 1.4 estimated million deaths per year and multidrug-resistant/rifampicin-resistant tuberculosis (MDR/RR-TB) is a major public health issue worldwide. [4] Chronic HCV-infection is estimated at 7% among active tuberculosis patients, [5] reaching up to 30% in some settings among MDR/RR-TB.…”
Section: Introductionmentioning
confidence: 99%